ISOLATION OF SEA BUCKTHORN RHIZOSPHERE MICROORGANISMS - Artikova Ra’no Ma’murovna; Abduraximova A’lonurxon Abdusalom (Web of Journals Publishing, 2024)
Isolation of beneficial microorganisms living in a symbiotic state around the root of a small plant under laboratory conditions and studying their diversity. Identifying phytohormone properties useful for the growth of other plants in these microorganisms.
Keywords: Retail, microorganism, microbiological analysis, nutrient medium, soil dilution, drug, phytohormonal properties.